Chemical Composition and In Sacco Degradation of Fish Waste Meal as Alternative Protein Feed Source - Safitri, Maurinda (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study was done to evaluate chemical composition and in sacco degradability of fish waste meal. Fresh fish (Congresox talabon) waste meal used in this study was collected from fish crackers industries of Indramayu, West Java. Fresh fish waste samples were dried and ground prior to be analyzed. The sample was analyzed for chemicals composition (dry matter, ash, crude protein, crude fiber, and crude fat) and incubated using nylon bag technique in 2 rumen fistulated Bali cattle to determine its dry matter, organic matter, and crude protein degradability. The results showed that fish waste meal contains a high level of crude protein (56.4%), fat (13.1%), and ash (27.3%), which showed its potency as protein and mineral source. The in sacco data showed that DM, OM, and CP degradations were similar or slightly higher than a+b fraction (49.6, 55.5, and 54.7% vs. 49.6, 55.7, and 57.5%, respectively), which imply that fish waste meal was optimally degraded in the rumen.